Service Quality, Patient Satisfaction, and Challenges of Multi-Specialty Dental Clinics in Highly Urbanized Cities in Western Visayas, Philippines - Jasmine Joyce G. Mendez; John Clifford P. Salugsugan (Philippine Social Science Journal, 2025)
This mixed-methods study assessed service quality and patient satisfaction in multi-specialty dental clinics across highly urbanized cities in Western Visayas, Philippines. Using the SERVQUAL framework, quantitative surveys of 180 personnel and patients evaluated dimensions such as reliability and empathy, while qualitative interviews identified operational challenges in management, safety, and compliance. Findings indicated consistently high ratings for both service quality and satisfaction, establishing a significant positive correlation between them. The study concludes that operational efficiency, rigorous quality assurance, and strict regulatory adherence are essential for sustaining clinical excellence. Although limited by its urban focus and cross-sectional design, the results highlight the critical link between service standards and patient outcomes. Future research should expand the geographic scope, utilize longitudinal designs, and explore the impact of digital technologies on dental healthcare delivery to further validate these findings.